Bodies in Fragments: Anatomical Healing Votives - MORRIS, CHRISTINE (My University, 2014)
Bodies in Fragments: Anatomical Healing Votives is an exhibition of images and artefacts to accompany the IIHSA Day School February 8, 2014 ‘Doctors, Diseases and Divinities: Health and healing in the ancient world’. The exhibition includess: Terracotta armies: Cretan bodies in clay; Anatomical votives from Minoan peak sanctuaries; Bodies in metal: Greek anatomical votives (tamata); Worked in wax: anatomical votives from Cyprus; Moulding the body: wax votives from Fatima, Portugal.
Doctors, Diseases and Divinities: Health and healing in the ancient world (one day conference)
PUBLISHED
Trinity College Dublin
Keywords: Votives; Tamata; Digital Humanities; Identities in Transformation